2013
DOI: 10.1364/ol.38.002897
|View full text |Cite
|
Sign up to set email alerts
|

Distance dependence of energy transfer from InGaN quantum wells to graphene oxide

Abstract: We report the distance-dependent energy transfer from an InGaN quantum well to graphene oxide (GO) by time-resolved photoluminescence (PL). A pronounced shortening of the PL decay time in the InGaN quantum well was observed when interacting with GO. The nature of the energy-transfer process has been analyzed, and we find the energy-transfer efficiency depends on the 1/d² separation distance, which is dominated by the layer-to-layer dipole coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In addition, Figure 2C2 shows bare GO suspension of the same concentration. Since the distance between the QDs and GO is very crucial for non-radiative energy transfer between them as Lin et al (2013) recorded that quenching is not strongly observable at distances greater than 20 nm, so here the target bacteria (≈ 0.5×2 µm size) acts as a spacer between the donor and the acceptor hindering the photons transfer and keeping the fluorescence of QDs. Figure 2D shows a SEM micrograph of QDs-Ab conjugates are capturing to bacterial cells of E coli O157:H7.…”
Section: Optimization Of Fluorescence and Quenching Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Figure 2C2 shows bare GO suspension of the same concentration. Since the distance between the QDs and GO is very crucial for non-radiative energy transfer between them as Lin et al (2013) recorded that quenching is not strongly observable at distances greater than 20 nm, so here the target bacteria (≈ 0.5×2 µm size) acts as a spacer between the donor and the acceptor hindering the photons transfer and keeping the fluorescence of QDs. Figure 2D shows a SEM micrograph of QDs-Ab conjugates are capturing to bacterial cells of E coli O157:H7.…”
Section: Optimization Of Fluorescence and Quenching Processmentioning
confidence: 99%
“…If the sample does not have E. coli O157:H7, the test line will be efficiently quenched when adding GO by FRET, since the distance between QDs/Abs (donor) and GO (acceptor) is few nanometres (Gaudreau, Tielrooij, Prawiroatmodjo, Osmond, de Abajo, andKoppens, 2013, Lin et al, 2013). On the other hand, if the sample has E. coli O157:H7, it will be selectively captured by the specific QDs/Abs probe on the test line, then after adding GO, resonance energy transfer is hindered or minimally occurs since the distance between GO and QDs exceeds to more than 20 nm by the bacteria interference (Gaudreau et al, 2013, Lin et al, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of colloidal quantum well donors, a slight deviation from d −4 scaling was observed at short distances, which has been attributed to the larger lateral extent of the free excitons in the nanoplatelets, leading to a deviation from classical dipole emitter approximation . Few studies reported different distance dependencies such as d −2.5 and d −2 . However, these unexpected scaling terms could simply arise due to the unexpected experimental conditions (e.g., non‐smooth spacer layers) or potential charge transfer pathways.…”
Section: Two‐dimensional Materials As Efficient Exciton Sinksmentioning
confidence: 99%
“…Interestingly, in studies in which GO was used as the acceptor, quenching was observable at distances greater than 20 nm. [14] Graphene oxide has been reported to be a universal highly efficient long-range quencher of fluorescence. [7] Our group previously reported the extraordinary performance of GO as a quencher of QD fluorescence emission in the solid phase.…”
mentioning
confidence: 99%